Copper-catalyzed reactions of α, β-unsaturated N-tosylhydrazones with diaryliodonium salts to construct N-arylpyrazoles and diaryl sulfones. Issue 35 (24th August 2022) - Chen, Lian-Mei; Zhou, Chuang; Li, Jing; Li, Jun; Guo, Xiao-Qiang; Kang, Tai-Ran
Abstract : A Cu(OAc)2 -catalyzed reaction of α, β-unsaturated N -tosylhydrazones with diaryliodonium salts to give N -arylpyrazoles and an extra diaryl sulfone has been developed. This reaction took full advantage of the "waste" part of substrates to give an extra and valuable product. Abstract : Herein, an economical copper-catalyzed reaction of α, β-unsaturated N -tosylhydrazones with diaryliodonium salts to construct both N -arylpyrazoles and diaryl sulfones has been developed. Both the p -toluenesulfonyl anion and the 3-arylpyrazole intermediates were formed in situ from N -tosylhydrazones. Subsequently, the former reacted rapidly with diaryliodonium salts to give diaryl sulfones and aryl iodide intermediates, and the latter reacted with aryl iodide to give N -arylpyrazoles under copper-catalyzed conditions. Using unsymmetrical mesityl phenyliodonium salts as substrates, mesityl p -toluenesulfide was obtained as the major product. This reaction took full advantage of the "waste" part of substrates to form an extra diaryl sulfone.